The subjunctive, “unreal” uses of past forms and some related topics - (:unkn) unknown (My University, 2022)
This study guide contains rules and a set of exercises on the grammar of modern English, focusing on mastering the peculiarities of expressing hypothetical actions as opposed to real actions. The exercises are accompanied by examples and correlated with corresponding grammatical comments for guidance. The collection can also be used for self-assessment by students or for teachers to implement current or final evaluations. The manual is intended for 2nd-year students of the Faculty of Foreign Languages studying English as their first foreign language, as well as 3rd-year students studying English as their second foreign language.